Pembelajaran Berdiferensiasi pada Mata Pelajaran Biologi: Implementasi dan Pengaruhnya dalam Meningkatkan Hasil Belajar Siswa (Lembaga Pengembangan Kinerja Dosen, 2025)
Education that is adaptive to individual needs is one of the main demands in the implementation of the Independent Curriculum. This study aims to analyze the influence of differentiated learning on students' cognitive learning outcomes in Biology subjects, especially human respiratory system materials. The research was conducted at SMA Negeri 1 Tondano using a quantitative approach and quasi-experimental methods. The sample consisted of two classes: the experimental class that applied differentiated learning and the control class that followed conventional learning. The data collection instrument is in the form of learning outcome tests given before and after treatment. Data analysis was carried out using descriptive statistical tests and an independent t-test using SPSS Statistics 27. The results showed that the average posttest results of students in the experimental class were significantly higher than those in the control class. The calculated t value of 6.092 exceeds the table's t value of 1.99, indicating that differentiated learning substantially improves student learning outcomes. Differentiated learning provides space for students to learn according to their learning style and readiness level, increasing motivation and participation. The implications of this study confirm the importance of the role of teachers in designing student-centered adaptive learning strategies. These findings contribute to developing more responsive and contextual learning models at the secondary education level.